Hand Gesture Interface for Smart Operation Theatre Lighting - Joseph, Jessita; D S, Divya (International Journal of Engineering and Technology, 2018)
Operation theatre lighting system is a critical component in the operation theatre. Focusing the light to the area of surgery and varying the light intensity is manually done in currently available systems. Disruption of surgeonâ€™s attention and possibility of infection due to non sterilized hands is a major setback of the manual controlling method. This usually requires assistants to adjust the position and intensity of the light system by commands from the surgeon. So, designing an intelligent lighting system for operating theatre which can maintain the intensity values to the required level without shadow effect to the operation area is an important requirement. Proposed system makes use of accelerators in the gloves worn by surgeon so as to track hand movements. Pre defined hand movements can be configured to move the lighting system up, down, left or right. Accelerator input is interpreted for its corresponding movement by controller at transmitter side and it is wirelessly given to the receiver side using an nRF module. At the receiver side the incoming command from the nRF is taken and suitable response generated at the motor driver by the controller to move the lighting device. In the same way predefined hand signal can be used to vary the intensity of the light by using microcontroller to drive an LED driver.Â Â